Pengaruh Pemberian Ekstrak Jahe terhadap Penurunan Intensitas Dismenore pada Remaja - Mila Dwi Jayanti; Winarni Winarni (Jurnal Medika Nusantara, 2025)
Background: Dysmenorrhea occurs when the hormone prostaglandin increases excessively during menstruation. Dismenorrhea complaints in adolescents, when untreated, can cause discomfort that interferes with daily activities and school activities. Dysmenorrhea experienced by teenagers can be overcome by consuming ginger extract. Objective: To find out the impact of giving ginger extract on decreasing the intensity of dysmenorrheic pain in adolescents at ‘Aisyiyah Surakarta University. Research methods: This study uses a pre-experimental design with a one-group pretest-posttest approach with samples of 23 respondents. The measurement used the NRS (Numeric Rating Scale) and analyzed data using the Wilcoxon Sign Rank test. Result: It was found that of the 23 respondents before giving ginger extract the majority experienced severe pain (60.86%), and after being given ginger extract, the majority experienced mild pain (56.52%). In light of the Wilcoxon signed rank test p value <0,001 smaller than 0,05. Conclusion: at ‘Aisyiyah Surakarta University, we found that administering ginger extract reduced the severity of dysmenorrhea in adolescents.